Cell-level 3D reconstruction and quantification of the Drosophila wing imaginal disc. (6th May 2019) - Breen, David E.; Sui, Liyuan; Bai, Linge; Jülicher, Frank; Dahmann, Christian
We describe a set of techniques that, when applied to a 3D stack of confocal microscopy images, produces a volumetric model of an epithelial tissue as well as a mesh model of its apicolateral cell boundaries. Via a projection step, detailed 3D models that approximate the individual cells in the epithelium are then defined. Once the individual cells are generated, their apical face area, height and volume may be computed and visualised, providing quantitative and visual data about the patterns of cells within the tissue. We have applied the techniques to the analysis of the developing wing imaginal disc of a late-larval Drosophila melanogaster. Our techniques are being applied to a series of specimens in an investigation that intends to quantitatively substantiate observed cell shape changes that occur during wing imaginal disc development.